National assessment of pharmaceutical workforce and education using the International Pharmaceutical Federation's global development goals: a case study of Qatar - Banan Abdulrzaq Mukhalalati; Meram Mohamed Mahmoud Elsayed Ibrahim; Majdoleen Omar Al Alawneh; Ahmed Awaisu; Ian Bates; Lina Bader (Taylor & Francis Group, 2021)
Background The sustainable development goals were launched by the United Nations in 2015. Its fifth goal was describing the achievement of universal health coverage by 2030. This goal reaffirms the importance of investing in the development and training of the global health workforce. In alliance with this, the International Pharmaceutical Federation (FIP) has published reports about pharmacy workforce planning in several countries. However, data about Qatar were not included in these reports. In 2017, FIP developed a transformational roadmap of pharmaceutical workforce and education. One systematic framework component of the roadmap is the Pharmaceutical Workforce Development Goals (DG[w]s) that were released in late 2016 and subsequently incorporated into the more comprehensive Global Development Goals1 in 2020, encompassing not only workforce development, but additionally practice and pharmaceutical science development. This study aimed to evaluate the current situation of pharmacy workforce and education in Qatar in relation to the original 13 Pharmaceutical Workforce Development Goals (DG[w]s). The objective was to identify the gaps in pharmacy workforce and education and to recommend evidence-led strategies to be included in both the Ministry of Public Health and the Qatar University College of Pharmacy workforce development plans. Methods Three rounds of conventional Delphi technique were conducted with expert panels of key decision-makers in pharmacy practice from the College of Pharmacy at Qatar University and the Ministry of Public Health, utilizing the FIP's self-assessment survey. Qualitative content analysis was used to analyze and prioritize the identified gaps from the collected data. DG[w] was considered "met" if all the provided indicators were achieved, "partially met" if at least one of the indicators were achieved, and "not met" if none of the indicators were achieved Results The lack of competency framework (DG[w]5), workforce data (DG[w]12), and workforce policy formation (DG[w]13) are three major gaps in the provision of pharmaceutical workforce and pharmacy education in Qatar, influencing other DG[w]s. These gaps need to be addressed by the formation of Qatar Pharmaceutical Association through which academic, practice, and policymaking sectors can work together in developing health workforce intelligence system. Conclusion The results indicated that DG[w]s are interrelated and a gap in one goal can negatively influence others. Results and recommendations of this research will facilitate the implementation of strategic plans across leading pharmacy sectors to meet health needs in Qatar and achieve the third pillar of the Qatar National Vision 2030.